Insights into the growth of nanoparticles in liquid polyol by thermal annealing. Issue 16 (20th July 2021) - Chauvin, Adrien; Sergievskaya, Anastasiya; Fucikova, Anna; Corrêa, Cinthia Antunes; Vesely, Jozef; Cornil, Jérôme; Cornil, David; Dopita, Milan; Konstantinidis, Stephanos
Abstract : The abnormal growth of metal and metal-oxide nanoparticles under thermal treatment in a polyol solution is explained. The process also allows the catalysis of carbon dot formation and the reduction of copper oxide. Abstract : We report on the growth of metal- and metal-oxide based nanoparticles (NPs) in heated polyol solutions. For this purpose, NPs are produced by the sputtering of a silver, gold, or a copper target to produce either silver, gold, or copper oxide NPs in pentaerythritol ethoxylate (PEEL) which has been annealed up to 200 °C. The objective of the annealing step is the fine modulation of their size. Thus, the evolution of the NP size and shape after thermal annealing is explained according to collision/coalescence kinetics and the affinity between the metal-/metal-oxide and PEEL molecule. Moreover, highlights of few phenomena arising from the annealing step are described such as (i) the reduction of copper oxide into copper by the polyol process and (ii) the effective formation of carbon dots after annealing at 200 °C.